DIGITAL INDIA TRANSFORMATION: MOVING INDIA FORWARD - shikhar mittal, madhavi damle (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Digital India is the Government of India initiated a program where it aims at transforming India into a digitally empowered India. The program focuses on providing governance and services on demand, creating countrywide digital infrastructure, & digitally empowering citizens. This paper reflects a research attempt to understand the Digital India program and its possible impact on making India digitally ready. The paper explores various initiatives, opportunities, and challenges associated with the 9 pillars of Digital India which are Jobs in IT, Production of Electronics, Information to all, Early Harvest Programme, Broadband connections, eKranti, E-Governance, Public Internet Access and Universal Access to Phones. Where each of these projects seems to be helping and providing benefits to the people of India. Still, there are some challenges that the citizens are facing. To name some - illiteracy, socio-economic differences, technical & cultural constraints. This paper attempts to describe and discuss the journey of making India a Digital India as well as the issues and challenges faced along with possible future aspects. The research methodology is in the area of digital systems that are transforming India. It is a concept paper and a descriptive study of literature from reliable sources and reports.